(3GdCSWQdGHs - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3bGd GdCSWQdGH cdeI jhfGfjI , hCTgQ eG bjd ai eYfGg ejRGf GdTeS hgj BdI TQjaI JMhi Ydi CcKQ GdCYeGd GdfLhejI HGdbhI , hcGfJ JMhjgG HGdaYd s
(3BNQgG (B:s
(3hJNW ef cd fbWI NWG Ydi ESJbGeI eQcR GdUajMI , hJcJH Ydi GdCbSGe YOOgG ef NW GdeZQH Edi GdYdGeI , hef NW hJO GdCQV Edi GdYdGeI CjVkG Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3jdi GdeNWhW LOhd GdXd HGdGUGHY hGdCbOGe dchTjGQs
(3cJHJ Hbde ajg VHW HChdgG Jedc SfI (B869 (3g`s
(3ajgG CTcGds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs